INNOVATION AND INEQUALITY IN A SMALL WORLD - Ines Lindner; Holger Strulik (International Economic Review, 2020)
We present a multicountry theory of economic growth and R&D-driven technological progress in which countries are connected by a network of knowledge exchange. Technological progress in any country depends on the state of technology in the countries it exchanges knowledge with. The diffusion of knowledge throughout the world explains a period of increasing world inequality, followed by decreasing relative inequality. Knowledge diffusion through a small world network produces an extraordinary diversity of country growth performances, including the overtaking of individual countries and the replacement of the technologically leading country in the course of world development.
Keywords: 330